2007
DOI: 10.1038/sj.npp.1301424
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the β3-Adrenoceptor as a Novel Treatment Strategy for Anxiety and Depressive Disorders

Abstract: The characterization of the first selective orally active and brain-penetrant b 3 -adrenoceptor agonist, SR58611A (amibegron), has opened new possibilities for exploring the involvement of this receptor in stress-related disorders. By using a battery of tests measuring a wide range of anxiety-related behaviors in rodents, including the mouse defense test battery, the elevated plus-maze, social interaction, stressinduced hyperthermia, four-plate, and punished drinking tests, we demonstrated for the first time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 39 publications
5
74
2
Order By: Relevance
“…Adapted from similar behavioral assays that model social anxiety-like states (Bailey and Crawley, 2009;Bruchas et al, 2011;Felix-Ortiz and Tye, 2014;Silverman et al, 2010), the social approach assay measures the time a mouse spends in the presence of a novel conspecific (social zone) (Figure 2a). Less time spent in the social zone indicates a social anxiety-like state that is reversible using traditional anxiolytics, such as diazepam (Stemmelin et al, 2007). We first demonstrated that animals expressing the empty vector eGFP control virus (n = 15) or rM3Ds BLA/CaMKIIα (n = 11) spent similar amounts of time investigating the empty cup (Figure 2b and c, top panels and Figure 2d; unpaired Student's t-test; t (24) = 1.109, P = 0.2785).…”
Section: Chemogenetic Activation Of Gαs Signaling In the Bla Is Suffimentioning
confidence: 99%
“…Adapted from similar behavioral assays that model social anxiety-like states (Bailey and Crawley, 2009;Bruchas et al, 2011;Felix-Ortiz and Tye, 2014;Silverman et al, 2010), the social approach assay measures the time a mouse spends in the presence of a novel conspecific (social zone) (Figure 2a). Less time spent in the social zone indicates a social anxiety-like state that is reversible using traditional anxiolytics, such as diazepam (Stemmelin et al, 2007). We first demonstrated that animals expressing the empty vector eGFP control virus (n = 15) or rM3Ds BLA/CaMKIIα (n = 11) spent similar amounts of time investigating the empty cup (Figure 2b and c, top panels and Figure 2d; unpaired Student's t-test; t (24) = 1.109, P = 0.2785).…”
Section: Chemogenetic Activation Of Gαs Signaling In the Bla Is Suffimentioning
confidence: 99%
“…It is reported that SR58611A displays high efficacy and potency at the rat and humanβ3 receptor. The selectivity for rat β3 are 280-and 140-fold compared with β1 andβ2 receptors, and is inactive at a number of other central targets involved in the regulation of stress-related disorders [18]. Several studies reported that SR58611A has antidepressant effects in the animal model of depression [19].…”
Section: Discussionmentioning
confidence: 99%
“…In order to prove SR58611A has anti-depressant properties, some researchers placed cortical electrodes on the sensorimotor cortex of rats for reliable visual discrimination of wakefulness, slow-wave sleep and rapid eye movement or paradoxical sleep. In summary, although there is limited evidence, but there are some evidence that the pharmacological stimulation of β 3 -Adrenoceptor may represent an innovative approach for the treatment of depressive disorders [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…113 Curiously, an agonist at ␤ 3 receptors (essentially absent from healthy adult human brain, although data for depressed tissue do not appear to be available) was in development for depression, but was recently discontinued. 114,115 As regards 5-HT, the traditional candidates are 5-HT 1A receptors. This has never been clinically proven, not least owing to poor tolerability of agonists.…”
Section: Recruiting Subsets Of Postsynaptic Sites Mediating Beneficiamentioning
confidence: 99%